LANGUAGE STYLE USED IN OLYMPUS HAS FALLEN - Andriani, Monika; Sari, Dian Purnama (LINGUA LITERA : journal of english linguistics and literature, 2023)
Abstract Language style is used by humans to convey meaning in different depending on their situation of speaking. People even mix their language styles based on context. It makes every human unique since it creates different language style because of their personality and situation in communication. The researcherss found it interesting to analyze the language style used in literary work. Therefore, this research discussed about the types of language style used in movie script, especially Olympus Has Fallen. Qualitative method is applied to conduct this study. The researcherss collected the data by u s i n g non-participant observation and audio-visuals material. The researcherssgot the data by analyzing the script. After that, the researcherss marked theutterances used by the actors and actresses. The researcherss used theory of Keraf (2009) to classify the types of language style. They are formal style, informal style and conversational style. After doing this research, the researcherss found all the types of language styles that mentioned by Keraf (2009). The researcherss found 102 data that were categorized into types of language style that used in movie script of Olympus Has Fallen. The results were classified into 12 data of formal style with 12 data, informal style with 25 data, and conversational with 65 data. The findings were dominated by conversational language style because the conversation is indeed used in daily context by using jargon, idioms, abbreviation, and slang. Overall, the researchers hope this research can add insight in the field of linguistics.